2015
DOI: 10.1007/s00381-015-2755-x
|View full text |Cite
|
Sign up to set email alerts
|

A case of relapsing spinal atypical teratoid/rhabdoid tumor (AT/RT) responding to vinorelbine, cyclophosphamide, and celecoxib

Abstract: The peculiarity of this case report is the clinical-radiological response to a metronomic therapy in a case of early-relapsing spinal AT/RT despite previous maximal surgery, chemotherapy, and radiotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 11 publications
0
16
0
Order By: Relevance
“…Furthermore, it has been shown that infected cells can bioactivate CPA, and the active chemotherapeutic metabolites can diffuse and kill non-infected bystander tumor cells 26, 28, 29. Because CPA is commonly used in chemotherapy regimens to treat both medulloblastoma and AT/RT, we postulated that studies investigating its inclusion with rRp450 in the treatment regimen were rational and may yield similar improvements 30, 31, 32, 33, 34. To evaluate the sensitivity to CPA in the context of rRp450 infection, we infected medulloblastoma and AT/RT cells with rRp450 in the presence or absence of CPA.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it has been shown that infected cells can bioactivate CPA, and the active chemotherapeutic metabolites can diffuse and kill non-infected bystander tumor cells 26, 28, 29. Because CPA is commonly used in chemotherapy regimens to treat both medulloblastoma and AT/RT, we postulated that studies investigating its inclusion with rRp450 in the treatment regimen were rational and may yield similar improvements 30, 31, 32, 33, 34. To evaluate the sensitivity to CPA in the context of rRp450 infection, we infected medulloblastoma and AT/RT cells with rRp450 in the presence or absence of CPA.…”
Section: Discussionmentioning
confidence: 99%
“…[ 7 10 11 12 ] Better prognoses correlate with older age, localized disease, and adequate resection. [ 5 ]…”
Section: Discussionmentioning
confidence: 99%
“…Findings within the spinal cord are rare. In particular, there have been only five prior cases of primary spinal AT/RT in adult patients[ 3 5 6 12 14 ] [ Table 1 ]. Patients typically present with axial neck or back pain and radiculopathy; only one exhibited cauda equina syndrome requiring acute surgical resection and decompression.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations